KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA DIKAJI DARI SELF CONCEPT SISWA DI KELAS VII - Sari, Yunita; Halini, Halini; Ijuddin, Romal (UNIVERSITAS TANJUNGPURA, 2023)
This study is a descriptive study that discusses problem solving mathematics that has high, medium, and low self-concepts on algebraic material at MTs Darul Hidayah. The subjects in this study were seventh grade students of MTs Darul Hidayah who were in high, medium, and low self-concept classes. Data collection techniques are test techniques and direct communication techniques. Data collection tools used were questionnaires, problem questions, and interviews. Obtained from Students with high self-concept able to understand problems, able to plan problem solving, able to solve problems according to plan, and able to prove answers by re-examining the results that have been obtained; Students with moderate self-concept are able to understand problems, are able to plan problem solving, and are able to solve problems according to plan; Students with low self-concept are able to understand problems, able to plan problem solving, able to solve problems according to plan but with inappropriate final results.